Distribution of the Ideology of Terrorism in the Youth Environment: Modern Realities and Directions of Counteraction - P. A. Merkulov (Управленческое консультирование, 2019)
This article analyzes the current practice of spreading terrorism in Russia and abroad. The causes and factors influencing the spread of the ideology of terrorism among youth are identified. It is proved that one of the main factors that influenced the spread of international terrorism was the “color revolutions” whose main actor was precisely the youth. The current trends in the development of terrorist activity and the involvement of young people in this activity are analyzed. On the basis of the analysis carried out, directions for counteracting and preventing the development of a terrorist ideology in the youth community have been proposed.